Educational action of the nurse in primary care: a view of arterial hypertension patients - Márcia Astrês Fernandes, Aline Raquel de Sousa, Mariza Márcia Rodrigues Gomes, Patrícia Maria Gomes de Carvalho, Augusto Everton Dias Castro (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v2i2.972